Biomarkers for non-small cell lung cancer immunotherapy - D. A. Kharagezov; Yu. N. Lazutin; E. Yu. Zlatnik; A. B. Sagakyants; E. A. Mirzoyan; A. G. Milakin; O. N. Stateshny; A. V. Chubaryan; I. A. Leyman (Южно-Российский онкологический журнал)
The discovery of immune checkpoint inhibition has revolutionized the treatment of many solid malignancies, including non-small cell lung cancer (NSCLC). Immune checkpoint inhibitors (ICI) can restore the antitumor immune response by blocking the inhibition of T-cell activation. Anti-programmed death-ligand 1 (PD-L1) is currently the main biomarker of the effectiveness of anti-PD-1 / PD-L1 blockade in the treatment of NSCLC without driver mutations. High tumor mutational burden suggests an increased neoantigens load and has been associated with the effectiveness of ICI therapy. Microsatellite instability, a biomarker approved for immunotherapy across solid tumors, but it is uncommon in NSCLC. Primary resistance to ICIsis characteristic of NSCLC with driver mutations, acquired is associated with immunoediting resulting in the depletion of potentially immunogenic neoantigens. The review discusses recent advances and future directions for predicting the results of immunotherapy in patients with NSCLC.